2020
DOI: 10.31234/osf.io/4z62t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psycho-social factors associated with mental resilience in the Corona lockdown

Abstract: The SARS-CoV-2 pandemic is not only a threat to physical health but is also having severe impacts on mental health. While increases in stress-related symptomatology and other adverse psycho-social outcomes as well as their most important risk factors have been described, hardly anything is known about potential protective factors. Resilience refers to the maintenance of mental health despite adversity. In order to gain mechanistic insights about the relationship between described psycho-social resilience facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
74
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 44 publications
14
74
0
5
Order By: Relevance
“…In addition, the present study further demonstrates that not only the frequency but also-and even stronger-the daily duration as well as the diversity of media exposure are significantly positively correlated with global symptom severity and therefore emphasize the meaning of mental distress associated with COVID-19 media coverage, particularly once a "critical load" has been reached. This conclusion is supported by both a recent study that turned out media coverage as one of the strongest emotional stressors in the context of the current pandemic [17] and the data of the present trial. Although it is not clear if psychological strain is rather a consequence or a cause of more immoderate media exploitation, we found the frequency and the duration of COVID-19 related media exposure to be positively correlated with the subjective need for its reduction due to a substantial amount of topic-induced stress.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the present study further demonstrates that not only the frequency but also-and even stronger-the daily duration as well as the diversity of media exposure are significantly positively correlated with global symptom severity and therefore emphasize the meaning of mental distress associated with COVID-19 media coverage, particularly once a "critical load" has been reached. This conclusion is supported by both a recent study that turned out media coverage as one of the strongest emotional stressors in the context of the current pandemic [17] and the data of the present trial. Although it is not clear if psychological strain is rather a consequence or a cause of more immoderate media exploitation, we found the frequency and the duration of COVID-19 related media exposure to be positively correlated with the subjective need for its reduction due to a substantial amount of topic-induced stress.…”
Section: Discussionsupporting
confidence: 88%
“…Former trials reported about significant psychological strain or distinct mental conditions resulting from crisis-related media coverage [13][14][15] and individual vulnerability was suspected to account significantly for this risk [16]. In the context of the current pandemic, up-to-date data also suggest that topic-specific media reporting results in a high level of stress in the vast majority of people [17]. However, we are aware of only one study that addressed the influence of COVID-19 related media exposure on stress-related mental symptoms so far.…”
Section: Introductionmentioning
confidence: 99%
“…The most vulnerable patients in our study, i.e., those with the highest levels of psychological distress, were people with lower baseline cognitive abilities and increased neuropsychiatric symptoms at baseline (i.e., collected before the COVID-19 pandemic), as well as low (perceived) social support and specific personality characteristics such as low trait resilience, low optimism, and high neuroticism. This is in line with previous studies in healthy people [ 28, 38, 39 ]. Longitudinal follow-up of our cohort might reveal which factors remain correlated with changes in psychological distress over time.…”
Section: Discussionsupporting
confidence: 94%
“…Data were loaded into IBM SPSS Statistics 23 to calculate sum-scores for the validated scales and to perform statistical testing. Positive appraisal and behavioral coping were calculated as described by Veer et al (2020) [28]: positive appraisal included the average of all 12 CERQ item scores and the 2 humor sub scores of COPE, for behavioral coping we took the average of the remaining 8 COPE items [28]. First, we conducted Pearson correlation analyses among cumulative stressor load, PSS and MDS-UPDRS-self, prior to performing a mediation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Auch wenn hier die Kausalrichtung nicht festzustellen ist, können Personen mit einer hohen affektiven Risikowahrnehmung als eine wichtige Zielgruppe identifiziert werden, da sie offensichtlich gut durch die Gesundheitsbehörden erreichbar sind. So sollten Behörden diesen nicht nur konkrete Handlungsempfehlungen zur Risikoreduktion anbieten, sondern auch Informationen zur Bewältigung eventueller psychologischer Belastungen, die bei Personen mit hoher affektiver Risikowahrnehmung ebenfalls höher sind [ 22 ].…”
Section: Diskussionunclassified